2021
DOI: 10.1111/1556-4029.14695
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a fluorescent dye to visualize touch DNA on various substrates

Abstract: The ability to visualize the presence of cellular material deposited by touch onto items of forensic importance has the potential to greatly aid in criminal investigations. It is now routine in forensic casework to examine items for DNA assumed to have been deposited by touch [1-3]. Such DNA is often referred to as 'touch DNA' even though samples collected from such deposits can also include DNA from undetermined biological sources other than that derived from skin and/or background DNA from actions other than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…DNA losses were quantified with mock fingerprints deposited on four different surfaces to better understand DNA collection and extraction method performance [ 189 ]. The application of Diamond Dye has been shown to enable visualization of cells deposited on surfaces without interfering with subsequent PCR amplification and DNA typing [ [190] , [191] , [192] ].…”
Section: Advancements In Current Practicesmentioning
confidence: 99%
“…DNA losses were quantified with mock fingerprints deposited on four different surfaces to better understand DNA collection and extraction method performance [ 189 ]. The application of Diamond Dye has been shown to enable visualization of cells deposited on surfaces without interfering with subsequent PCR amplification and DNA typing [ [190] , [191] , [192] ].…”
Section: Advancements In Current Practicesmentioning
confidence: 99%
“…Visualisation of touch DNA – Several papers referred to Diamond™ Nucleic Acid Dye to emphasize the genetic material contained in fingermarks [ [469] , [470] , [471] , [472] , [473] , [474] , [475] , [476] ]. Some ridge details could be observed, but this approach was mostly presented to emphasize areas of interest or investigate shedder status.…”
Section: Fingermark Visualisationmentioning
confidence: 99%
“…The use of fluorescent nucleic acid staining dyes (e.g., Diamond™ dye, SYBR® Green I, and GelGreen™) has been developed recently for detecting latent DNA on items [5,[11][12][13][14][15][16]. A recent study reported monitoring the deposited cell number within entire thumbprints on a glass slide through a "single touch" event using DD staining [6]; however, a comparison of the visualized cells number from the entire and a part of the thumbprint was not part of this report [6].…”
Section: Highlightsmentioning
confidence: 99%